Przyczyny pomijania zalecanych dawek leków przez pacjentów z jaskrą - Kowal, Małgorzata; Chorągiewicz, Tomasz; Mietlicka, Katarzyna; Wyszyńska, Anna; Żarnowski, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: Aim of the study was to identify obstacles to medication adherence (compliance) for patients with glaucoma. Material and methods: A prospective case series of structured interviews were conducted in 150 patients with glaucoma. (75 patients treated in the glaucoma out-patient clinic of the Department of Ophthalmology, Medical University, Lublin, Poland and 75 patients treated in regional out-patient clinics). Questionnaire of an anonymous survey, formulated on the basis of the publication: Tsai J.C. et al. “Compliance barriers in glaucoma: a systematic classification”, J. Glaucoma. 2003, 12, 393-398. Results: The results of the survey showed omissions of particular doses of medications in 62.7% of patients from regional outpatient clinics and in 35.3% of patients treated at the Department of Ophthalmology. It was shown that 32.7% of respondents from regional outpatient clinics and 8.7% from the Department of Ophthalmology Glaucoma Clinic declared remaining without antiglaucoma drops for more than one day. As reasons for omissions of single doses of the medications: forgetfulness (54.7%), too many doses of medications (10%) and little knowledge about the disease (10%) were usually pointed. According to the respondents: little knowledge (32%) and financial factors (22%) are the main causes of medications withdrawal for longer time. Conclusions: The most common obstacles to medication compliance for patients with glaucoma include: forgetfulness, low level of knowledge about the disease, financial factors and too many doses of the medications. Fewer doses and the presence of a supporting person have a positive influence on compliance.